Development of electrically conductive microstructures based on polymer/CNT nanocomposites via two-photon polymerization - Staudinger, Ulrike; Zyla, Gordon; Krause, Beate; Janke, Andreas; Fischer, D.; Esen, Cemal; Voit, Brigitte; Ostendorf, Andreas (Microelectronic Engineering, 2017)
Femtosecond laser-induced two-photon polymerization (2PP) of carbon nanofiller doped polymers was utilized to produce electrically conductive microstructures, which are expected to be applicable as microelectronic components or micro-electromechanical systems in sensors. The nanocomposites were processed by compounding an inorganic-organic hybrid material with two different types (short and long) of single walled carbon nanotubes (SWCNTs). Different SWCNT contents were dispersed in the polymer by sonication to adjust the electrical conductivity of the nanocomposites. Low surface resistivity values of 4.6 × 105 Ω/sq. could be measured for coated reference films with a thickness of 30 μm having an exceptionally low SWCNT content of 0.01 wt% of the long type of SWCNTs. In contrast, a higher minimum resistivity of 1.5 × 106 Ω/sq. was exhibited for composites with a higher content, 2 wt%, of short SWCNTs. The structural quality of the microstructures processed by 2PP was mainly influenced by the dispersion quality of the SWCNTs. To characterize the electrical conductivity, conductive atomic force microscopy was applied for the first time. In microstructures with 0.05 wt% of the long type of SWCNTs, a contact current could be detected over a wide range of the measured area visualizing the electrical conductive CNT network, which has not been reported before.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Carbon nanotube; Conductive nanocomposite; Microstructure; Two-photon polymerization